The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1111/j.1365-2672.1998.tb05296.x
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter epidemiology: an aquatic perspective

Abstract: SUMMARY Members of the genus Campylobacter have established themselves as the most common human gastro‐enteric pathogens throughout much of the developed world. The ubiquitous distribution of Campylobacter spp. in animal reservoirs and food products derived thereof make such vehicles primary risk factors in contracting campylobacteriosis. The contamination rates, identification of common pathogenic serotypes and extended survival of Campylobacter in surface waters illustrates the potential, but yet to be quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 57 publications
(32 reference statements)
2
60
2
1
Order By: Relevance
“…Waterborne outbreaks caused by campylobacters have been reported especially in countries where groundwater sources that are not chlorinated are commonly used as the drinking water supply (2,15,16,17,18,25,31). In Finland, almost 1,500 small drinking water plants use groundwater as a raw water source, and they distribute approximately 45% of the total amount of drinking water consumed (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Waterborne outbreaks caused by campylobacters have been reported especially in countries where groundwater sources that are not chlorinated are commonly used as the drinking water supply (2,15,16,17,18,25,31). In Finland, almost 1,500 small drinking water plants use groundwater as a raw water source, and they distribute approximately 45% of the total amount of drinking water consumed (18).…”
Section: Discussionmentioning
confidence: 99%
“…Microbiological analysis is an additional tool for safety assessment. In confirmed waterborne outbreaks, however, when epidemiological studies have indicated that drinking water is the source of the infection, coliforms or E. coli has not always been detected either in source or net water samples (1,5,15,17,31,32). One reason for the low detection rate may be too few samples combined with sample volumes that are too small (100 ml).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…For a pathogen that is so difficult to culture in a laboratory, Campylobacter have been shown to have a rather remarkable capacity for survival in aquatic environments (42). Indeed, it appears that greater numbers of pathogens are found in aquatic environments during winter and spring periods because of the relatively lower water temperatures in winter (43).…”
Section: Review • Skelly and Weinsteinmentioning
confidence: 99%
“…The use of Campylobactercontaminated water to wash vegetables may result in banking the organism on the surface of the product. Also, leafy vegetables irrigated with untreated water or cultivated in Campylobacter contaminated soils are likely to carry the pathogen (Thomas et al, 1999).…”
Section: Introductionmentioning
confidence: 99%